A confirmed case of macrophage activation syndrome secondary to spotted fever rickettsiosis: Response to immunomodulation in a pediatric patient in northeastern, Mexico - Galindo Hayashi, Jose Marcelo; Sifuentes-Aguilar, Laura I; Soto-Chavez, Poleth M; Ramos-Ortiz, Cesar A; Villarreal-Treviño, Ana V (Indian Journal of Case Reports, 2024)
An 8-year-old girl with a rash and high-grade fever for 6 days arrived at the emergency room. She had an erythematous macular rash on the face, trunk, arms, and legs. Further interrogation called attention to the presence of close contact with stray dogs. Her town had been recognized as a site of a rickettsiosis outbreak in the past year. Spotted fever rickettsiosis was suspected, and doxycycline treatment was initiated. Macrophage activation syndrome (MAS) secondary to Rickettsia rickettsii infection was diagnosed according to the Hemophagocytic lymphohistiocytosis and EULAR/PRINTO/PRES 2016 criteria. As there are no clear guidelines on the treatment of MAS secondary to R. rickettsii. the course of action taken by the pediatric intensive care unit team was to avoid disseminated intravascular coagulopathy and treat MAS, both life-threatening conditions. Directed therapy with high doses of methylprednisolone and intravenous immunoglobulin therapy was initiated. The patient recovered, regaining her functional state before the illness. Few articles have described the association between MAS and rickettsiosis, an illness with high mortality, which makes it paramount to detect and treat promptly.